g(x) = x-6 is the function g(x) = x with a negative vertical shift of 6. That is to say, take the whole graph of g(x) = x and move it down 6 units.
Chat with our AI personalities
Graph that equation. If the graph pass the horizontal line test, it is an inverse equation (because the graph of an inverse function is just a symmetry graph with respect to the line y= x of a graph of a one-to-one function). If it is given f(x) and g(x) as the inverse of f(x), check if g(f(x)) = x and f(g(x)) = x. If you show that g(f(x)) = x and f(g(x)) = x, then g(x) is the inverse of f(x).
I will use the quotient rule here. d/dx(f(x)/g(x) = g(x)*f'(x) - f(x)*g'(x)/[g(x)]2 x3*1/x - ln(x)*3x2/(x3)2 x3/x - 3ln(x)x2/x6 x2 - 3ln(x)x2/x6 = - 3ln(x)/x4 =========
y=x+1 there for answer is 2
y equals x-4 plus 2 is the same as y = x-2. You just translate the graph of y=x, 2 units to the right, OR 2 down.
It is translated left 8 and up 4.